ABOUT THE POSSIBILITY OF UPGRADING THE AC LOCOMOTIVES WITH TRACTION COMMUTATOR MOTORS - Bezruchenko, V. M.; Hilievych, O. I.; Mukha, O. M.; Shapovalov, O. V. (Science and Transport Progress, 2007)
The article considers issues of introducing new modes of traction collector electric motors operation and application of static converters with the purpose of improving the power performances of a.c. electric locomotives.